Exploring the Caregiver Role after Deep Brain Stimulation Surgery for Parkinson’s Disease: A Qualitative Analysis - Suzette Shahmoon; Patricia Limousin; Marjan Jahanshahi (Parkinson's Disease)
This pilot study aimed to explore how caregiver spouses make sense of themselves one and five years after their partner’s deep brain stimulation (DBS) surgery for Parkinson’s disease. 16 spouse (8 husbands and 8 wives) caregivers were recruited for the interview. Eight struggled to reflect on their own lived experience and primarily focused on the impact of PD on their partners, such that their transcripts were no longer viable for interpretative phenomenological analysis (IPA). A content analysis showed (1) how these 8 caregivers shared less than half as many self-reflections than the other caregivers, (2) that there was a bias to reflect on their partner’s experience answering the opening question, (3) the bias continued when answering subsequent questions, and (4) there was a lack of awareness of this bias. No other patterns of behaviour or themes were able to be extracted. The remaining 8 interviews were transcribed and analysed using IPA. This analysis discovered 3 inter-related themes: (1) DBS allows carers to question and shift the caregiver role, (2) Parkinson’s unites and DBS divides, and (3) seeing myself and my needs, DBS enhances visibility. How these caregivers interacted with these themes depended on when their partners were operated. The results suggested that spouses maintained the role of caregiver one year post DBS because they struggle to identify themselves in any other way but were more comfortable reassociating into the role of spouse 5 years post surgery. Further inquiry into caregiver and patient identity roles post DBS is recommended as a means of supporting their psychosocial adjustment after surgery.